A pre and post intervention study to reduce unnecessary urinary catheter use on general internal medicine wards of a large academic health science center - Krista R. Wooller; Chantal Backman; Shipa Gupta; Alison Jennings; Delvina Hasimja-Saraqini; Alan J. Forster (BMC, 2018)
Abstract Background Urinary catheters are a common medical intervention, yet they can also be associated with harmful adverse events such as infection, urinary tract trauma, delirium and patient discomfort. The purpose of this study was to describe the use of the SafetyLEAP program to drive improvement efforts, and specifically to reduce the use of urinary catheters on general internal medicine wards. Methods A pre and post intervention study using the SafetyLEAP program was performed with urinary catheter prevalence as the primary outcome on two general internal medicine wards in a large academic health sciences center. Results A total of n = 534 patients (n = 283 from ward #1; and n = 252 from ward #2) were included in the initial audit and feedback portion of the study and 1601 patients (n = 824 pre-intervention and n = 777 post-intervention were included in the planned quality improvement portion of the study). A total of 379 patients during the quality improvement intervention had a urinary catheter. Overall, the adherence to the SafetyLEAP program was 97.4% on both general internal medicine wards. The daily catheter point prevalence decreased from 22 to 13%. After the implementation of the program, the urinary catheter utilization ratio (defined as urinary catheter days/patient days) declined from 0.14 to 0.12. Catheter-associated urinary tract infections (CAUTI) were unchanged. Conclusion The SafetyLEAP program can help provide a systematic approach to the detection, and reduction of safety incidents. Future studies should aim at refining and implementing this intervention broadly.